2017
DOI: 10.1093/ajh/hpx026
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Proatrial Natriuretic Peptide with Components of the Metabolic Syndrome in Adolescents and Young Adults from the General Population

Abstract: The young adults displayed significant negative associations between MR-proANP and several components of the metabolic syndrome, whereas such associations were not found among the adolescents besides triglycerides and diastolic BP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
0
7
1
1
Order By: Relevance
“…Nevertheless, other studies have found associations between copeptin and the metabolic factors related to IR in children and adolescents [18][19][20], but the associations found have overall been less consistent compared with the studies in adults [2][3][4][5][6][7][8]. We have no obvious explanation for this age-related discrepancy, but it is important in this connection that the well described negative association between insulin and IR and the natriuretic peptide system could not be found among our adolescents, either [39], and that others have also found that age modulates the association of copeptin with IR [40]. Accordingly, in a family-based crosssectional study, the association between copeptin and IR could only be found among the middle-aged and elderly but not among the younger adults [40].…”
Section: Adolescents Versus Young Adultscontrasting
confidence: 88%
“…Nevertheless, other studies have found associations between copeptin and the metabolic factors related to IR in children and adolescents [18][19][20], but the associations found have overall been less consistent compared with the studies in adults [2][3][4][5][6][7][8]. We have no obvious explanation for this age-related discrepancy, but it is important in this connection that the well described negative association between insulin and IR and the natriuretic peptide system could not be found among our adolescents, either [39], and that others have also found that age modulates the association of copeptin with IR [40]. Accordingly, in a family-based crosssectional study, the association between copeptin and IR could only be found among the middle-aged and elderly but not among the younger adults [40].…”
Section: Adolescents Versus Young Adultscontrasting
confidence: 88%
“…Twenty-seven studies 20,21,2426,3134,38,39,41,43,48,49,51,5458,60–64,66 reported the association between cardiac NPs and TC, for a total of 43428 subjects evaluated. Twenty-eight studies 2025,2730,3234,3739,44,45,51,52,5557,59,61,63,64,66 reported the association between cardiac NPs and LDLc, for a total of 44829 subjects evaluated. Thirty-six studies 20,21,2426,3134,38,39,41,43,48,49,51,5458,60–64,66 reported the association between cardiac NPs and HDLc, for a total of 49951 subjects evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-six studies 20,21,2426,3134,38,39,41,43,48,49,51,5458,60–64,66 reported the association between cardiac NPs and HDLc, for a total of 49951 subjects evaluated. Thirty-nine studies 2030,3242,4447,5057,5964 reported the association between cardiac NPs and TG, for a total of 39649 subjects evaluated. All the components of lipid profile was associated with NPs.…”
Section: Resultsmentioning
confidence: 99%
“…Natriuretic peptides inhibit pathways involved in inflammation and attenuate the production of proinflammatory cytokines by macrophages and adipocytes. 179,227 Importantly, circulating levels of natriuretic peptides are decreased in obesity, diabetes, metabolic syndrome and non-alcoholic fatty liver disease, particularly in women [228][229][230][231] ; in addition, these disorders are accompanied by impaired responsiveness to the actions of natriuretic peptides in adipose tissue, blood vessels and the kidney. [232][233][234] The impairment of natriuretic peptide signalling may be related to an increase in neprilysin that is seen in states of visceral adiposity 185 ; enhanced neprilysin activity has been implicated in the end-organ injury seen in diabetes.…”
Section: Role Of Aldosterone Leptin and Natriuretic Peptides In The mentioning
confidence: 99%